Given data:
The given graph of the polynomial.
The value of the given polynomial is zero, at x=-3, -1, and 3.
Substitute -3 for x in the expression of the first polynomial.
![\begin{gathered} f(-3)=(-3)^3+(-3)^2-9(-3)-9 \\ =-27+9+27-9 \\ =0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sl6ddn8n90jb3jro8ydy856118mbb16e9k.png)
Substitute -1 for x in the expression of the first polynomial.
![\begin{gathered} f(-1)=(-1)^3+(-1)^2-9(-1)-9 \\ =-1+1+9-9 \\ =0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tgfdzq94vb51i4hi4raxd1qrpeplsq68rl.png)
Substitute 3 for x in the expression of the first polynomial.
![\begin{gathered} f(3)=(3)^3+(3)^2-9(3)-9 \\ =27+9-27-9 \\ =0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/fj7evgup3rnlunu6nkdn4cclpwl65yvalh.png)
As all the points are satisfied for the first option.
TThus, the first option is correct.